Antibiofilm, antiquorum sensing and antioxidant activity of secondary metabolites from seeds of Annona senegalensis, Persoon. (July 2020) - Tamfu, Alfred Ngenge; Ceylan, Ozgur; Fru, Godloves Chi; Ozturk, Mehmet; Duru, Mehmet Emin; Shaheen, Farzana
Abstract: The increasing resistance of bacteria to antibiotics has motivated the interest in potent natural compounds capable of disrupting bacterial cell-to-cell communication. Column chromatography of seed extract of Annona senegalensis afforded N -cerotoyltryptamine (1 ), asimicin (2 ) and ent-19-carbomethoxykauran-17-oic acid (3 ). The compounds were tested for their antimicrobial, antibiofilm, and anti-quorum sensing activities. The minimum inhibitory concentrations (MIC) values ranged from 50 μg/mL to 100 μg/mL for C. albicans ATCC 10239 and S. aureus ATCC 25923 E. coli ATCC 25922, C. violaceum CV026 and C. violaceum CV12472. All the compounds inhibited biofilm formations of all microorganisms tested in various percentages at MIC and MIC/2. Compound 2 also exhibited the highest antibiofilm activity against C. albicans (yeast) and E. coli with percentage inhibitions ranging from 6.3 ± 4.1 (MIC/4) to 37.9 ± 4.5 (MIC) for C. albicans and from 18.8 ± 1.1 (MIC/4) to 43.2 ± 0.5 (MIC) for E. coli . Compound 1, however, showed highest biofilm inhibition on S. aureus as the percentage inhibition varied from 26.7 ± 3.6 (MIC/4) to 43.8 ± 2.1 (MIC). Compound 2 showed highest percentage violacein inhibition on C. violaceum CV12472 ranging from 10.2 ± 0.5 (MIC/8), 65.76 ± 1.3 (MIC/2) and 100 (MIC). Compound 1 and 3 had percentage violacein formation inhibitions on C. violaceum CV12472 ranging from 9.66 ± 1.1 (MIC/4) to 100 (MIC), and from 17.4 ± 2.4 (MIC/4) to 100 (MIC), respectively. Swimming and swarming motility of P. aeruginosa PA01 strain was evaluated at three concentrations of 50, 75 and 100 μg/mL. The compounds inhibited the P. aeruginosa swimming and swarming motility at the three tested concentrations (50, 75 and 100 μg/ml) in a dose-dependent manner. The extents of inhibition of motility migration was relatively higher in the swimming model than in the swarming model for all compounds. Compound 1 exhibited the highest percentage inhibition of motility of 41.50 ± 3.5 and 39.73 ± 1.5 in swimming model and swarming model respectively at 100 μg/ml. Compound 3 showed the lowest percentage inhibition of 30.36 ± 2.0 and 23.50 ± 2.5 in swimming and swarming respectively at 100 μg/ml. At the lowest tested concentration of 50 μg/ml, it was compound 2 showing the highest inhibition of motility of 17.49 ± 0.5 and 14.29 ± 1.0 in swimming and swarming respectively. Compound 1 showed highest quorum sensing (QS) activity with QS inhibition zone of 20.0 ± 1.5 mm at MIC and 11.0 ± 1.0 mm at MIC/8 while compound 2 had the highest antimicrobial (AM) zone diameter amongst the compounds at MIC. Compound 3 was the QS inhibitory sample and did not show any QS inhibition at MIC/8 while showing its highest QS inhibition zone of 13.0 ± 1.6 mm at MIC. For antioxidant assays, no sample showed better activity than the standards. Compound 2 had highest activity with IC50 values of 87.79 ± 2.70 and 42.77 ± 1.53 μg/mL in DPPH and β-carotene-linoleic acid assay respectively and was more active (IC50 of 97.69 ± 1.40 μg/mL) than standard quercetin (IC50 250.09 ± 0.87 μg/mL) in metal chelation assay. Highlights: N-cerotoyltryptamine, asimicin and ent-19-carbomethoxykauran-17-oic acid from Annona senegalensis Persoon inhibited bacterial growth and prevented biofilm formation by C. albicans ATCC 10239, S. aureu s ATCC 25923 and E. coli ATCC 25922. Bacterial cell-to-cell communication was disrupted as revealed by percentage inhibition of violacein formation by C. violaceum CV12472 and anti-quorum sensing assay on the mutant strain CV026. The compounds reduced bacterial swarming and swimming motilities on P. aeruginosa PA01. The compounds showed moderate antioxidant activities.